Absent right superior vena cava. (25th January 2021) - Hayashi, Takahiro; Murakami, Masato; Saito, Shigeru
Abstract : A patient planned to be performed catheter ablation. However, three‐dimensional contrast‐enhanced chest computed tomography revealed isolated persistent left superior vena cava. We should know such an anatomical abnormality especially when central venous catheter or peripherally inserted central catheter is inserted from right jugular vein or right subclavian vein